Pengaruh Literasi Keuangan, Penggunaan E-money, dan Pengendalian Diri terhadap Perilaku Konsumtif Generasi Z di Kota Bandung - Sari, Rista Asmaya; Manjaleni, Rola (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to analyze the influence of financial literacy, e-money usage, and self-control on the consumptive behavior of Generation Z in Bandung City. Generation Z tends to have a high level of consumptive behavior due to the advancement of digital technology and the ease of access to cashless transactions. This study employs a quantitative method with a purposive sampling technique, involving 100 respondents who actively use e-money. Data analysis is conducted using multiple linear regression tests. The findings reveal that financial literacy has a negative impact on consumptive behavior, while e-money usage has a significant positive influence on consumptive behavior. Additionally, self-control acts as a moderating factor that can mitigate the negative effects of e-money usage on consumptive behavior. The implications of this study highlight the importance of financial education for Generation Z to enhance awareness of wiser financial management in the digital era.